Analisis Kasus Kecelakaan Pemboran pada Industri Migas di PT.X berdasarkan Faktor Manusia Tahun 2022 - Khodijah, Siti; Wirawan, Mufti (UI Scholars Hub, 2023)
Oil and gas drilling activities have associated high risks. 80% of the causes of drilling accidents are caused by human performance. In 2020, drilling activities at PT. X accounts for 3 out of 8 accidents and the common cause that occurs due to human factors. Unsafe acts are the main cause of drilling accidents in the oil and gas industry. This study discusses the analysis of cases of oil and gas drilling accidents at PT.X from the point of view of human factors. The purpose of this study is to analyze the contributing factors of active and latent failure and to analyze cases of work accidents from the point of view of human factors in drilling activities at PT. X year 2022, and determine recommendations for future improvements from drilling activities at PT. X. This research method uses descriptive analytic from secondary data and interview results. It was found that the latent condition that contributed to the drilling accident that occurred at PT. X in 2022, namely failure to update the latest regulations, the control carried out is still administrative in nature, etc. While active failures that contribute are failure to interpret damaged equipment, SOP violations, etc. So, it was found that latent conditions contributed more to cause unsafe acts. The synthesis of the analysis results obtained shows that the safety value has not been embedded in PT. X. So, the recommendation given by the author is to make OHS a safety of work.